2021
DOI: 10.1111/hex.13239
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to optimize patient and family engagement in hospital planning and improvement: Qualitative interviews

Abstract: Background Patient engagement (PE) in health‐care planning and improvement is a growing practice. We lack evidence‐based guidance for PE, particularly in hospital settings. This study explored how to optimize PE in hospitals. Methods This study was based on qualitative interviews with individuals in various roles at hospitals with high PE capacity. We asked how patients were engaged, rationale for approaches chosen and solutions for key challenges. We identified themes using content analysis. Results Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 21 publications
0
37
0
1
Order By: Relevance
“…Medical personnel should initiatively communicate with patients, encourage patients to express confusions, consider patients as the cooperative partner. Anderso et al 34 found that cooperative participation will be developed and accepted as a mainstream form of patient participation; therefore, medical staff should also actively pay attention to the desire of patients to participate in information interaction, meet the information needs of patients in a variety of ways and take the initiative to provide patients with disease‐ and treatment‐related information in the process of communication and interaction between medical staff and patients. Different communication skills should be utilized to optimize the communication process, to improve the quality of communication, to ensure that patients correctly understand the information provided on SSI and, with the help of mobile medical technology, to provide patients with continuous and comprehensive information to fully grasp the relevant knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical personnel should initiatively communicate with patients, encourage patients to express confusions, consider patients as the cooperative partner. Anderso et al 34 found that cooperative participation will be developed and accepted as a mainstream form of patient participation; therefore, medical staff should also actively pay attention to the desire of patients to participate in information interaction, meet the information needs of patients in a variety of ways and take the initiative to provide patients with disease‐ and treatment‐related information in the process of communication and interaction between medical staff and patients. Different communication skills should be utilized to optimize the communication process, to improve the quality of communication, to ensure that patients correctly understand the information provided on SSI and, with the help of mobile medical technology, to provide patients with continuous and comprehensive information to fully grasp the relevant knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Medical personnel should initiatively communicate with patients, encourage patients to express confusions, consider patients as the cooperative partner. Anderso et al 34 found that cooperative participation will be developed and accepted as a mainstream form of patient participation; therefore, medical staff should also actively pay attention to the desire of patients to participate in information interaction, meet the information needs of patients in a variety of ways and take the initiative to provide patients with disease-and treatment-related information in the process of communication and interaction between medical staff and patients.…”
Section: Thoughts and Suggestions On Promoting Rational Participation In The Prevention And Control Of Ssi In Crc Patientsmentioning
confidence: 99%
“…As a result, the hospital converted 11 million American dollar losses into four million profits after four years of implementation [25]. Since then, BSC has gained increasing attention, and many HCO in high-income countries and low-and middle-income countries have strategically utilized BSC to develop their organizations [28][29][30][31][32].…”
Section: Figure (1): Balanced Scorecard Perspectivesmentioning
confidence: 99%
“…Another review [28] revealed that there had been a lack of engaging stakeholders in BSC implementations, such as engaging patients and HCWs. However, researchers have pointed to the importance of patient and HCW engagement in the process of PE and delivery improvement [29][30][31]. The rest of the BSC reviews [28,[32][33][34][35][36][37][38][39][40][41][42] focused only on the general narration of the BSC perspectives and subdimensions used.…”
Section: Figure (2): Duke University Health System Strategic Mapmentioning
confidence: 99%
See 1 more Smart Citation